2012
DOI: 10.7439/ijbar.v3i11.816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postural Challenges on Non-invasive Cardiac Output Measurement with Impedance Cardiography in Young Healthy Adults Using New Horizontal Electrode Placement Method.

Abstract: Background: Cardiac output is an important hemodynamic parameter of cardiovascular system and a significant indicator of autonomic function status of a person. It can be measured invasively as well as non-invasively. Imepdance cardiography (ICG) is a promising, new, noninvasive technique to measure cardiac output. There are no studies noninvasively measuring cardiac output in healthy subject by impedance cardiography using new horizontal method of electrode placement during postural challenges. Objective: We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, thigh CSA muscle , SupV, DA and DV were larger when upright possibly because of the orthostatic challenge [29], whereas the COMP applied in the current study may not be sufficient to overcome the orthostatic-induced tissue engorgement [15]. In the upright position, CO and SV were lower [31,32], therefore higher HR was observed to compensate for the orthostatic challenge [32,33]. A previous study showed that 60 mmHg would completely occlude vessels in the upright position in leg pain patients [15], however the COMP applied to significantly compress thigh tissues and its effects in healthy populations warrants further investigation.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, thigh CSA muscle , SupV, DA and DV were larger when upright possibly because of the orthostatic challenge [29], whereas the COMP applied in the current study may not be sufficient to overcome the orthostatic-induced tissue engorgement [15]. In the upright position, CO and SV were lower [31,32], therefore higher HR was observed to compensate for the orthostatic challenge [32,33]. A previous study showed that 60 mmHg would completely occlude vessels in the upright position in leg pain patients [15], however the COMP applied to significantly compress thigh tissues and its effects in healthy populations warrants further investigation.…”
Section: Discussionmentioning
confidence: 58%
“…Although the mechanism of the abnormal cerebral blood flow reduction in ME/CFS patients is not fully understood, one of the hypothesized mechanisms is that the abnormal cerebral blood flow reduction is related to an abnormal cardiac output reduction due to increased venous pooling and lack of venous return during the tilt test ( Timmers et al, 2002 , van Campen and Visser, 2018a ). It has previously been shown in healthy controls that cardiac output returns to normal pre-tilt test values within 1 min of the supine recovery phase ( Barde and Deepak, 2012 , Miyake et al, 2014 , Toska and Walløe, 2002 ). In ME/CFS patients the cardiac output in the post-test supine recovery phase has not been studied previously.…”
Section: Introductionmentioning
confidence: 97%